Prognostic stratification of older patients with multivessel coronary artery disease treated with percutaneous transluminal coronary angioplasty based on clinical and biochemical measures: protocol for a prospective cohort study. Issue 2 (28th February 2022) - Carmona-Segovia, Ada del Mar; Doncel-Abad, María Victoria; Becerra-Muñoz, Víctor M; Rodríguez-Capitán, Jorge; Sabatel-Pérez, Fernando; Flores-López, María; Sánchez-Quintero, María José; Medina-Vera, Dina; Molina-Ramos, Ana Isabel; El Bekay, Rajaa; Morales-Asencio, José Miguel; Angullo-Gómez, María; et al.
Abstract : Introduction: The incidence of acute coronary syndrome is rising in step with the growth of life expectancy. An increase in the age of patients with coronary artery disease has been related to in-hospital mortality, which has seen an upsurge over a short period of time. However, there is no consensus about the percutaneous coronary angioplasty strategy to follow for older patients with multivessel coronary artery disease (MVCAD). Complete revascularisation (CR) or incomplete revascularisation (ICR) strategy depends on prognosis but this has not yet been accurately described because of geriatric conditions and comorbidities. The aim of this study is to evaluate changes of clinical and biochemical parameters in older patients with MVCAD undergoing revascularisation and to establish a prognostic stratification model for CR and ICR. Methods and analysis: This observational, longitudinal, prospective study will include 150 patients with MVCAD and subsequent revascularisation who attend the Hospital Universitario Virgen de la Victoria (Málaga, Spain). Because of the dropout rates, 180 patients will be recruited at the beginning. Sociodemographic characteristics, clinical and angiographic parameters, and biochemical variables, such as cardiovascular, metabolic, inflammatory, stress oxidative biomarkers, will be collected in the admission for coronary revascularisation and three follow-ups at 6, 12 and 18 months. Statistical analyses will be conducted with these data using CR and ICR as the primary exposure variable. Relevant explanatory variables will be selected from a predictive model for their inclusion in a prognostic stratification model. The primary outcome measures will be major adverse cardiovascular events. Ethics and dissemination: Protocols and patient information have been approved by the regional research ethics committee (CEIm Provincial de Málaga-PEIBA (PI0131/2020). The results will be disseminated in international peer-reviewed journals, presented at conferences in Cardiology and Gerontology, and sent to participants, medical and health service managers, clinicians and other researchers.